Reformulation of Bundo Kanduang's Role in Solving Domestic Violence Cases - Suryani, Irma; Yulnetri, Yulnetri; Amrina, Amrina; Nengsih, Ifelda; Randawar, Daleleer Kaur (Universitas Negeri Gorontalo, 2023)
This study aims to reevaluate the role of Bundo Kanduang in addressing Domestic Violence cases within the Minangkabau indigenous community in West Sumatra. Utilizing qualitative research methods, data collection tools include documents, interviews, and Focus Group Discussions (FGD). The study involves Bundo Kanduang Adat and household members within the Bundo Kanduang organization in Tanah Datar, Agam, and Fifty Cities, totalling 35 participants per regency. Data analysis consists of three stages: Reduction, Presentation, and Verification. Method triangulation compares interview outcomes with FGD results for data triangulation. Theoretical triangulation is then applied to reassess Bundo Kanduang's role in resolving domestic violence cases. The findings reveal that Bundo Kanduang's role in addressing domestic violence under Minangkabau customary tambo has been implemented socially but not optimally within families due to factors such as low education, demanding work schedules, children relocating after marriage, and a lack of concern for one's hometown. To ensure the effective implementation of Bundo Kanduang's role in combating domestic violence, the following reformulations are proposed: 1) Leveraging the